2019
DOI: 10.3390/s19051127
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of an Analyte Concentration in Test Solution by Using Helmholtz Resonator for Biosensor Applications

Abstract: In this paper, an indirect method of measuring an analyte concentration in a test solution using the resonant frequency change of a Helmholtz resonator is proposed, using a novel architecture of Helmholtz resonator filled with two kinds of fluids (fixed fluid and test solution). Since the analyte concentration yields changes of density and sound speed of the test solution, the resonant frequency of the proposed Helmholtz resonator is affected by the analyte concentration of the test solution. From this effect,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, the billions of batteries produced each year are unsustainable, their disposal poses environmental problems, and their limited service life poses a challenge to the long-term/autonomous operation of the devices. The rapidly growing market for solid-state electronics is leading the development of ultra-low-power devices and self-powered devices [1], such as wearable electronic devices [2], biosensors [3], IoT and remote sensors [4,5]. Accordingly, the world is very interested in reducing carbon dioxide emissions and developing more renewable energy technologies to generate electricity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the billions of batteries produced each year are unsustainable, their disposal poses environmental problems, and their limited service life poses a challenge to the long-term/autonomous operation of the devices. The rapidly growing market for solid-state electronics is leading the development of ultra-low-power devices and self-powered devices [1], such as wearable electronic devices [2], biosensors [3], IoT and remote sensors [4,5]. Accordingly, the world is very interested in reducing carbon dioxide emissions and developing more renewable energy technologies to generate electricity.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmad et al [11] designed a flow-based electromagnetic energy harvester using a microplanar coil for IoT sensor applications. The prototype volume was 291.4 cm 3 and experimentation indicated that it was able to generate a 686 µW of maximum power at an operating flow rate of 12 L/min at the optimal matching impedance. Liu et al [12] presented a non-resonant rotational electromagnetic energy harvester for harvesting irregular human motions.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few of the aforementioned sensors has focused on the sensitivity of minute change of the glucose concentration. In most cases, the sensitivity is larger than 20 mg dL −1 …”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the sensitivity is larger than 20 mg dL −1 . [2,3,9,10] Metamaterials are artificial electromagnetic (EM) structures composed of subwavelength resonators with narrow-spectral feature, which are well suitable for sensing applications. [11,12] Localized surface plasmons (LSPs) arise from electron resonances of the nanoparticle surface and applied EM fields, which can produce significant local field enhancements [13][14][15] and are highly sensitive to the particle geometry and local dielectric environment.…”
mentioning
confidence: 99%